Denn sie wissen, was sie tun: Das Geschäft mit Kleinwaffen - Schmidt, Dorothea (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
In the last years, on average 300.000 people were killed each year in armed conflicts, 200.000 civilians died by the use of small arms in non-military situations. The constant supply of second-hand and new arms manufactured mostly by American and European producers and the easy accessibility in many regions of the world help to nurture violence and conflict situations. Producers and their supporters like the US-American NRA claim „Guns don’t kill people. People kill people” and stress that they always act within the legal framework. Nevertheless, producers are frequently trying to circumvent and undermine or campaigning for the abolishment of all kinds of regulations. Therefore they also bear responsibility for the dreadful damages of the use of small arms.